Increasing the quality and power capacity of HERIC PV-Inverter through multilevel topology implementation. (August 2019) - Hamid, M I; Ardiansyah, D
Abstract: In photovoltaic generation applications, high efficiency and good output power quality inverter are very important. The most common way to improve the quality of the inverter output voltage is to increase the switching frequency. However, at the same time, this method will increase power losses. This paper introduces a new topology inverter: HERIC multilevel, as an inverter that has good voltage quality (low THD) with a low switching frequency. This topology was tested and analyzed by performing simulations to compare it with the conventional HERIC and cascaded H-Bridge inverters. The results prove that the multilevel HERIC inverter has a lower THD compared to the two inverters. At the switching frequency of 2500Hz; Multilevel HERIC inverters have THD, 1.23%, cascaded H-bridge has 1.34% THD, and conventional HERIC THD 11.4%.